(untitled) (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2013)
Class III malocclusions are considered one of the most complex and difficult orthodontic problems to diagnose and treat. Skeletal and/or dental asymmetries in patients presenting with Class III malocclusions can worsen the prognosis. Recognizing the dentoalveolar and skeletal characteristics of Class III malocclusions and their treatment possibilities is essential for a favorable nonsurgical correction. Therefore, this article presents a nonsurgical extraction approach to Class III malocclusion treatment which can significantly improve the occlusal and facial discrepancies. DOI: http://dx.doi.org/10.3329/bjodfo.v2i1.15999 Ban J Orthod & Dentofac Orthop, October 2011; Vol-2, No.1, 20-25